FLOOD MANAGEMENT IN THE AREA OF PEJATEN EDUCATIONAL AND CULTURAL COMPLEX SOUTH JAKARTA - Imamuddin, Mohammad; Alisjahbana, Sofia W.; Ma’some, Dadang (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Educational and Cultural Complex Area Waterway is located in Pasar Minggu District. There is connecting Waterway (PHB Pulo), which floods every rainy season. It is due to the non-technical cross-section of the waterway, sedimentation, and garbage on the west side. The obstructed flow direction is found in the elegant Pejaten housing, where the high water level of PHB Pulo causes the water to slow down. From the above conditions, it is necessary to normalize the cross-section of 1 x 1 m2 using concrete / u-ditch to accommodate five-year rainfall of 2,305 m3/second, with a pump capacity to accelerate the flow to PHB Pulo by 1 m3/second.